Evaluation and Management of Early Onset Genetic Obesity in Childhood - Malhotra, Sonali; Sivasubramanian, Ramya; Srivastava, Gitanjali (Journal of Pediatric Genetics, 2021)
One in five children and adolescents in the United States are diagnosed with obesity and nearly 6% of them are being classified under the severe obesity category. With over 7% of severe obesity being attributed to genetic disorders, in this review we aim to focus on monogenic and syndromic obesity: its etiology, wide spectrum of clinical presentation, criticalness of early identification, and limited management options. Advanced genetic testing methods including microarray and whole genome sequencing are imperative to identify the spectrum of mutations and develop targeted treatment strategies including personalized multidisciplinary care, use of investigational drugs, and explore surgical options in this unique subset of severe pediatric obesity.
Keywords: infantile obesity; genetic obesity; hyperphagia; weight-for-length percentile; pediatric weight management; pediatric obesity